Suppression of anger and subsequent pain intensity and behavior among chronic low back pain patients: the role of symptom-specific physiological reactivity - Burns, John W. (2011)
Suppression of anger may be linked to heightened pain report and pain behavior during a subsequent painful event among chronic low back patients, but it is not clear whether these effects are partly accounted for by increased physiological reactivity during suppression. Chronic low back pain patients (N = 58) were assigned to Suppression or No Suppression conditions for a “cooperative” computer maze task during which a confederate harassed them. During baseline and maze task, patients' lower paraspinal and trapezius muscle tension, blood pressure and heart rate were recorded. After the maze task, patients underwent a structured pain behavior task (behaviors were videotaped and coded). Results showed that: (a) Suppression condition patients revealed greater lower paraspinal muscle tension and systolic blood pressure (SBP) increases during maze task than No Suppression patients (previously published results showed that Suppression condition patients exhibited more pain behaviors than No Suppression patients); (b) residualized lower paraspinal and SBP change scores were related significantly to pain behaviors; (c) both lower paraspinal and SBP reactivity significantly mediated the relationship between Condition and frequency of pain behaviors. Results suggest that suppression-induced lower paraspinal muscle tension and SBP increases may link the actual suppression of anger during provocation to signs of clinically relevant pain among chronic low back pain patients.